1999
DOI: 10.1073/pnas.96.21.11792
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal DNA binding stimulates N-terminal phosphorylation of the outer membrane protein regulator OmpR from Escherichia coli

Abstract: Expression of the porin genes of Escherichia coli is regulated in part by the osmolarity of the growth medium. The process is controlled by the histidine kinase EnvZ and the response regulator OmpR. We have previously shown that phosphorylation of OmpR increases its affinity for the upstream regulatory regions of ompF and ompC. We now report that, in the presence of DNA, there is a dramatic stimulation in the level of phospho-OmpR. This effect is independent of the source of phosphorylation, i.e., stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
92
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 62 publications
12
92
1
Order By: Relevance
“…The above results indicate that OmpR-P binding to DNA is essential for the observed accumulation of OmpR-P by DNA, consistent with the previous observation (24). We further tested this notion with OmpR N (residues 1-134).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The above results indicate that OmpR-P binding to DNA is essential for the observed accumulation of OmpR-P by DNA, consistent with the previous observation (24). We further tested this notion with OmpR N (residues 1-134).…”
Section: Resultssupporting
confidence: 77%
“…g OmpR was phosphorylated with 50 M [␥-32 P]ATP by 60 g glutathione S-transferase (GST)-EnvZc11, a GST fusion of a superkinase mutant, EnvZcT247R, in 200 l of buffer A containing 5 mM Ca 2ϩ at room temperature for 1 h. HPLC C4 column analysis (24) demonstrated that more than 95% OmpR in the reaction has been converted into OmpR-P (data not shown). The reaction mixture was stopped by addition of 10 mM EDTA and then applied to a Sephacryl S-100 HR gel-filtration column (0.8 ϫ 10 cm; Amersham Pharmacia) to separate GST-EnvZc11 from OmpR-P and to remove free [␥-32 P]ATP and inorganic phosphate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a linker of 20 amino acid residues should provide a similar increase in local concentration of the amino and carboxyl termini as a linker of 15 amino acid residues, it seems likely that the linker of OmpR plays some active role in directing the appropriate interaction between the two domains (13, 39, 40). Evidence supporting this view comes from our studies of limited proteolysis with trypsin, in which we found that cleavage sites in the linker were sensitive to both phosphorylation and DNA binding in the amino-and carboxylterminal domains, respectively (13,41).…”
Section: Discussionmentioning
confidence: 56%
“…Phosphorylation of OmpR at the aminoterminal aspartate 55 increases the DNA binding affinity of the carboxyl terminus (9 -12). Conversely, the presence of specific DNA binding sites increases the steady-state amount of OmpR-P formed in vitro (13,14). Our laboratory is interested in determining the mechanism responsible for this interdomain communication in OmpR.…”
mentioning
confidence: 99%